Intraoperative liver deformation and organ motion caused by ventilation, laparotomy, and pneumoperitoneum in a porcine model for image-guided liver surgery - Wise, Philipp; Preukschas, Anas; Özmen, Emre; Bellemann, Nadine; Norajitra, Tobias; Sommer, Christof-Matthias; Stock, Christian; Mehrabi, Arianeb; Müller, Beat P.; Kenngott, Hannes Götz; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2024)
Background: Image-guidance promises to make complex situations in liver interventions safer. Clinical success is limited by intraoperative organ motion due to ventilation and surgical manipulation. The aim was to assess influence of different ventilatory and operative states on liver motion in an experimental model.Methods: Liver motion due to ventilation (expiration, middle, and full inspiration) and operative state (native, laparotomy, and pneumoperitoneum) was assessed in a live porcine model (n = 10). Computed tomography (CT)-scans were taken for each pig for each possible combination of factors. Liver motion was measured by the vectors between predefined landmarks along the hepatic vein tree between CT scans after image segmentation.Results: Liver position changed significantly with ventilation. Peripheral regions of the liver showed significantly higher motion (maximal Euclidean motion 17.9 +/- 2.7 mm) than central regions (maximal Euclidean motion 12.6 +/- 2.1 mm, p < 0.001) across all operative states. The total average motion measured 11.6 +/- 0.7 mm (p < 0.001). Between the operative states, the position of the liver changed the most from native state to pneumoperitoneum (14.6 +/- 0.9 mm, p < 0.001). From native state to laparotomy comparatively, the displacement averaged 9.8 +/- 1.2 mm (p < 0.001). With pneumoperitoneum, the breath-dependent liver motion was significantly reduced when compared to other modalities. Liver motion due to ventilation was 7.7 +/- 0.6 mm during pneumoperitoneum, 13.9 +/- 1.1 mm with laparotomy, and 13.5 +/- 1.4 mm in the native state (p < 0.001 in all cases).Conclusions: Ventilation and application of pneumoperitoneum caused significant changes in liver position. Liver motion was reduced but clearly measurable during pneumoperitoneum. Intraoperative guidance/navigation systems should therefore account for ventilation and intraoperative changes of liver position and peripheral deformation.
Online veröffentlicht: 26. Dezember 2023
Gesehen am 06.08.2024